2009
DOI: 10.2478/v10086-009-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Usability of some plant protein ingredients in the diets of Siberian sturgeon Acipenser baerii Brandt

Abstract: Abstract. This study investigated the effect of partially replacing fish meal (FM) in diets with plant protein ingredients on the growth, feed intake, feed efficiency, and nutrient retention of Siberian sturgeon, Acipenser baerii Brandt, juveniles. FM was replaced with soy protein concentrate (SP) and rape meal (RM). Three experimental feeds (40% crude protein, 10% fat) were prepared by extrusion. The protein sources in diet FM were fish meal, blood meal, and fish hydrolysate. In diet SP, the fish meal and fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…A similar trend was observed in the present study, but crude protein in whole fish body was not significantly reduced by the dietary treatments. Similar results have previously reported in Nile tilapia (Azaza et al 2009) and Siberian sturgeon (Acipenser baerii) (Mazurkiewicz et al 2009) fed diets containing FBM and some plant protein ingredients, respectively.…”
Section: Body Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar trend was observed in the present study, but crude protein in whole fish body was not significantly reduced by the dietary treatments. Similar results have previously reported in Nile tilapia (Azaza et al 2009) and Siberian sturgeon (Acipenser baerii) (Mazurkiewicz et al 2009) fed diets containing FBM and some plant protein ingredients, respectively.…”
Section: Body Compositionsupporting
confidence: 90%
“…Such a process can be described by reduced deposition of fat in the fish received these treatments, which influenced the size of the liver. On the other hand, no changes were observed in body lipid contents with the addition of vegetable protein in the diet of Siberian sturgeon (A. baerii) (Mazurkiewicz et al 2009). Our results agree with the results of Gaber (2006) and Azaza et al (2009), who reported a reduction tendency in body lipid content and an increasing trend in whole-body moisture content in Nile tilapia fish fed with high levels of broad bean meal (V. faba).…”
Section: Body Compositionmentioning
confidence: 96%
“…There are similar findings showing that protein requirement for optimum and maximum growth in white sturgeon larvae range from 40 to 50%, respectively (Hung 1991; Hung, 2000; Hung and Deng, 2002). However, there are other results showing that the optimum protein requirement for sub‐yearling sturgeon is somewhat lower approximating 40% (Stuart and Hung, 1989; Kaushik et al, 1989; Mohseni et al, 2007; Mazurkiewicz et al, 2009). A larger demand for protein appears to be related to fish age and/or size and supports the idea that dietary protein requirement diminishes as fish grows older (NRC, 1993; De Silva and Anderson, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The most available are plant meals. However, some plant meals resulted in growth depression, i.e., soybean meal (SBM) [43], soy protein concentrate, and rapeseed meal [55]. Other meals, such as sesame oil cake and corn gluten [37], caused a reduction in growth performance in cases with inclusion levels higher than 24% and was the same with wheat gluten [4].…”
Section: Introductionmentioning
confidence: 99%